Effect of interannual variations of Kuroshio–Tsushima Warm Current system on the transportation of juvenile Japanese jack mackerel (Trachurus japonicus) to the Pacific coast of Japan. (30th November 2022) - Igeta, Yosuke; Sassa, Chiyuki; Takahashi, Motomitsu; Kuga, Mizuki; Kitajima, Satoshi; Wagawa, Taku; Abe, Shoko; Watanabe, Chikako; Setou, Takashi; Nakamura, Hirohiko; Hirose, Naoki
Abstract: Recruitment of Japanese jack mackerel ( Trachurus japonicus ) has been decreasing continuously since 2000 in the Pacific coastal waters of Japan. The reasons and mechanisms for this phenomenon are still unclear. Particle‐tracking experiments were performed using a data assimilation model to elucidate the effect of a current system on the transportation processes of T. japonicus from the main spawning ground in the southern East China Sea to the Pacific coastal waters. The experiments demonstrated that T. japonicus were transported from the southern East China Sea to the Pacific waters around western Japan through the Tokara Strait, and the number of particles transported to the Pacific decreased from 2000 to 2017. The particles passing through the northwest Tokara Strait tended to be transported to the Pacific side during 2000–2005 and to the Sea of Japan during 2006–2017. The bifurcation toward the Sea of Japan was due to an amplification of the northward current where the Tsushima Warm Current originates (west of Kyushu). This change was induced by a rising sea level west of Kyushu due to Kuroshio's northward shift along the western Pacific coast of Japan, which induced the Tsushima Strait through flow to strengthen. The decrease in larval transportation due to the current system change can be one of the causes for the recruitment decline of T. japonicus along the Pacific coast.